2020
DOI: 10.1016/j.heliyon.2020.e03304
|View full text |Cite
|
Sign up to set email alerts
|

Overview of seasonal influenza and recommended vaccine during the 2016/2017 season in Nepal

Abstract: Background: Influenza is a highly contagious viral respiratory infection caused by influenza viruses whose epidemic and pandemic have resulted in significant morbidity and mortality. The annual epidemic of influenza results in an estimated 3-5 million cases of severe illness and about 290000-650000 deaths globally. The vaccination program has been successful to control the epidemic however, it further needs improvement. This study was aimed to investigate the types of influenza viruses prevailing in Nepal duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
(27 reference statements)
0
7
2
1
Order By: Relevance
“…A study conducted by Adhikari et.al also reported similar finding according to which pandemic influenza AH1N1 dominated in the year 2009 in Nepal 17 . However, different from previous study by Upadhayay et al and Jha et al which showed influenza A/H3 was responsible for 60.1% and 51.0% of the total infection in year 2014 and 2016 in Nepal respectively 8 , 15 . According to a study from tropical Asia, influenza A predominated over influenza B between 2007 and 2013, which is consistent with our study 18 .…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…A study conducted by Adhikari et.al also reported similar finding according to which pandemic influenza AH1N1 dominated in the year 2009 in Nepal 17 . However, different from previous study by Upadhayay et al and Jha et al which showed influenza A/H3 was responsible for 60.1% and 51.0% of the total infection in year 2014 and 2016 in Nepal respectively 8 , 15 . According to a study from tropical Asia, influenza A predominated over influenza B between 2007 and 2013, which is consistent with our study 18 .…”
Section: Discussioncontrasting
confidence: 62%
“…According to the World Health Organization, the H1N1pdm09 or H3N2 subtype of the influenza A virus has been co-circulating in the European region throughout the 2018–2019 flu season 14 . However, either influenza A(H1N1) pdm09 or A(H3N2) dominated (2014/15–2016/17) of influenza season 15 . Every season, a new strain or genetic variation of the influenza virus reemerges, bringing with it novel antigenic features that may reduce vaccine-induced protection due to strain mismatches between the vaccine and circulating strains.…”
Section: Discussionmentioning
confidence: 99%
“…(PTI, 2020b). Thus, the vaccine ‘Covishield’ developed by India was hailed as the ‘Sanjivini Buti’ – the life-saving intervention for Nepal during this difficult time, according to Jha (2021). With its dwindling influence in the region, India’s media reported that China had begun pressuring Nepal to accept China’s vaccine without verifying its efficacy and efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Dünya sağlık örgütü 2018-2019 sezonuna influenza A virüsünün hâkim olduğunu bildirdi 15 . İnfluenzanın mevsimsel dağılımını araştıran bir çalışmada Temmuz-Ağustos aylarında enfeksiyonun çoğundan influenza B sorumluyken, Ocak-Şubat aylarında İnfluenza A' nın daha baskın olduğu raporlandı 16 . Bizim çalışmamızda da influenza hızlı tanı testi pozitif örneklerin tamamında influenza A tespit edildi.…”
Section: Discussionunclassified